A mixed methods evaluation of Multiple Mini Interviews for entry into the Bachelor of Midwifery. Issue 2 (March 2023) - Sheehan, A.; Thomson, R.; Arundell, F.; Pierce, H.
Abstract: Background: Multiple-mini interviews (MMI) are increasingly used as part of the admission process into healthcare degrees. Evaluations have found MMIs to be a fair assessment tool in terms of reliability and validity and viewed positively by those involved in the MMI process. The use of MMIs in midwifery is novel and evaluation is lacking. Aim: To evaluate the use of MMIs as part of the admission process for the Bachelor of Midwifery in one Australian university. Methods: A basic convergent mixed methods study design was utilised. Data included linked data sets, Likert scale responses to survey questions, focus groups and open-ended survey questions. Integration took place at the interpretation and reporting stage. Findings: Participants viewed the MMI experience positively. The study confirmed the reliability of the MMIs as an assessment tool. Most variance in MMI scores was attributed to the candidate at 31.4 % with the interviewer and the interview station having less influence on the MMI score at 11 % and 6.4 % variance. Older applicants on average achieved higher MMI scores, and those who spoke a language other than English at home or were first in family to attend university had lower on average MMI scores. Being born overseas did not impact an applicant's MMI score. The overall experience was seen as fair, offering further opportunity to gain entry into the Bachelor of Midwifery. Conclusion: MMIs were viewed positively and findings support the use of MMIs as part of an admissions process for the Bachelor of Midwifery.